Measuring the contribution of Bt cotton adoption to India's cotton yields leap - Gruère, Guillaume P.; Sun, Yan (International Food Policy Research Institute, 2012)
While a number of empirical studies have demonstrated the role of Bt cotton adoption in increasing Indian cotton productivity at the farm level, there has been questioning around the overall contribution of Bt cotton to the average cotton yield increase observed these last ten years in India. This study examines the contribution of Bt cotton adoption to long- term average cotton yields in India using a panel data analysis of production variables in nine Indian cotton-producing states from 1975 to 2009. The results show that Bt cotton contributed 19 percent of total yield growth over time, or between 0.3 percent and 0.4 percent per percentage adoption every year since its introduction. Besides Bt cotton, the use of fertilizer and the increased adoption of hybrid seeds appear to have contributed to the yield increase over time. However, if official Bt cotton adoption contributed to increased yield after 2005, unofficial Bt cotton might also have been part of the observed increase of yields starting in 2002, the year of its official introduction in India.